Pemanfaatan Media Whatsapp dan Zoom dalam Pembelajaran Daring di SMAIT Asy-Syukriyyah - Setyawan, Aris (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2022)
This study aims to determine the effectiveness of whatsapp and zoom media in online learning at SMAIT Asy-Syukriyyah, especially in English learning. This study used qualitative research method. The data collection tehniques are observations, interviews, and documentation. This research was conducted from january 2021- march 2021 in XI sains grade at SMAIT Asy-Syukriyyah Tangerang. Based on the research resuts, it shows that whatsapp and zoom media are the effective media in online learning.